2017
DOI: 10.1371/journal.pone.0188337
|View full text |Cite
|
Sign up to set email alerts
|

Expert cognition in the production sequence of Acheulian cleavers at Gesher Benot Ya'aqov, Israel: A lithic and cognitive analysis

Abstract: Stone cleavers are one of the most distinctive components of the Acheulian toolkit. These tools were produced as part of a long and complex reduction sequence and they provide indications for planning and remarkable knapping skill. These aspects hold implications regarding the cognitive complexity and abilities of their makers and users. In this study we have analyzed a cleaver assemblage originating from the Acheulian site of Gesher Benot Ya‘aqov, Israel, to provide a reconstruction of the chaîne opératoire w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 24 publications
1
39
0
Order By: Relevance
“…However, it is our contention that the required cognitive abilities, including team work, social cooperation, communication skills and the production of a wide array of tools suitable for hunting (mostly made of perishable material such as wood), were all integral components of their abilities (see [28,97] for supporting data). Such abilities have already been suggested regarding the occupants of the Acheulian site of Gesher Benot Ya'akov, 780,000 years ago [30,164], who are known to have procured and eaten elephants [165]. Furthermore, the large quantities of fat and meat associated with elephants may imply the existence of some form of food sharing between group members and possibly between different groups, and/or preservation, as well as the existence of cooperative acquisition strategies [7].…”
Section: Discussionmentioning
confidence: 91%
“…However, it is our contention that the required cognitive abilities, including team work, social cooperation, communication skills and the production of a wide array of tools suitable for hunting (mostly made of perishable material such as wood), were all integral components of their abilities (see [28,97] for supporting data). Such abilities have already been suggested regarding the occupants of the Acheulian site of Gesher Benot Ya'akov, 780,000 years ago [30,164], who are known to have procured and eaten elephants [165]. Furthermore, the large quantities of fat and meat associated with elephants may imply the existence of some form of food sharing between group members and possibly between different groups, and/or preservation, as well as the existence of cooperative acquisition strategies [7].…”
Section: Discussionmentioning
confidence: 91%
“…A detailed examination of the distal configurations of the GBY cleavers has shown that three different modes were employed in their production ( Figure 2). This shows that the decision to produce a cleaver must have taken place in an early phase of the reduction sequence, prior to the modification of the slab fragment into a core (Herzlinger et al, 2017).…”
Section: Production Of Basalt Cleavers Technical Sequencementioning
confidence: 99%
“…It is an ecologically valid (Gobet, 2016) variety of thinking deployed in real-world circumstances, and relies on a medley or cognitive resources including perception, motor memory and control, routinized sequences, and executive decision making (de Groot, 1965;Gobet, 1998;Ericsson & Delaney, 1999;Ericsson et al, 2000;Gobet & Simon, 2000). Expert cognition is thus an appropriate cognitive model for interpreting Palaeolithic remains, especially the technical and foraging remains that constitute the vast majority of Palaeolithic evidence (Wynn & Coolidge, 2014;Herzlinger et al, 2017;.…”
Section: Gby Hominin Cognitionmentioning
confidence: 99%
See 2 more Smart Citations